2016
DOI: 10.1111/are.13102
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission and concurrent infection of multiple bacterial pathogens in naturally infected red tilapia (Oreochromisspp.)

Abstract: Horizontal transmission of various bacterial pathogens in tilapia is well described, but there is scant information regarding their vertical transmission. This study aimed to determine the possibility of vertical transmission of two commonly reported bacterial pathogens (Francisella noatunensis subsp. orientalis and Shewanella putrefaciens) in natural stocks of red tilapia (Oreochromis spp.). Vertical transmission of these pathogens via gametes was evaluated using in vitro fertilization from 10 different famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 41 publications
(54 reference statements)
0
25
0
Order By: Relevance
“…The tissue samples were obtained from 78 moribund and clinically healthy Nile tilapia, Oreochromis niloticus (L.) that were randomly collected from two different geographical locations including 38 fish from three tilapia farms in the UK (Farm one (Lincolnshire): 10 fish / 40±3 gm; Farm two (Lincolnshire): 10 fish /45±2 gm; Farm three (London): 18 fish / 12±5 gm) and 40 fish from a commercial tilapia farm in Prachinburi province, Thailand (10±2gm). The first and second UK farms and the Thai farm had a history of natural outbreaks of francisellosis during 2011–2012 and 2008, 2013–2014 respectively with granulomatous lesions in the affected fish and variable mortalities [ 4 , 29 , 33 ]. The third UK farm had no history of francisellosis, but it supplied red tilapia fry to an aquaponics farm in London, UK, where a natural outbreak of francisellosis occurred during spring 2017.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue samples were obtained from 78 moribund and clinically healthy Nile tilapia, Oreochromis niloticus (L.) that were randomly collected from two different geographical locations including 38 fish from three tilapia farms in the UK (Farm one (Lincolnshire): 10 fish / 40±3 gm; Farm two (Lincolnshire): 10 fish /45±2 gm; Farm three (London): 18 fish / 12±5 gm) and 40 fish from a commercial tilapia farm in Prachinburi province, Thailand (10±2gm). The first and second UK farms and the Thai farm had a history of natural outbreaks of francisellosis during 2011–2012 and 2008, 2013–2014 respectively with granulomatous lesions in the affected fish and variable mortalities [ 4 , 29 , 33 ]. The third UK farm had no history of francisellosis, but it supplied red tilapia fry to an aquaponics farm in London, UK, where a natural outbreak of francisellosis occurred during spring 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleic acid-based methods have been applied for Fno detection, including conventional polymerase chain reaction (PCR) [ 4 , 5 , 27 29 ], quantitative real time PCR (qPCR) [ 5 , 21 , 22 , 30 , 31 ], duplex PCR, in situ hybridisation [ 32 ] and loop mediated isothermal amplification (LAMP) [ 33 ]. Despite the fact that, these techniques have their own points of interest, downsides, for instance, time consuming [ 22 , 33 ], labour intensive, prerequisite for skilled staff, liability to give false negative or false positive results due to low sensitivity or specificity [ 21 ], high influence with reaction inhibitors [ 34 , 35 ] and requirement of complex design [ 33 ] make them more challenging to use for pond-site diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, a natural case of vertical transmission and co‐infections with Fno and Shewanella putrefaciens was reported for the first time from red tilapia ( Oreochromis spp.) broodstock (Pradeep et al, 2017). The authors' findings showed that both Fno (6/10) and S. putrefaciens (4/10) were transmitted vertically to the fertilized eggs.…”
Section: The Co‐infections In Tilapia: Types and Effectsmentioning
confidence: 99%
“…Morbidity and mortality of tilapia have been reported to be caused by co‐infections with A. hydrophila and S. agalactiae (Pradeep et al. ); A. veronii and Flavobacterium columnare (Dong et al. ); A. hydrophila , A. veronii , and Streptococus agalactiae (Liu et al.…”
Section: Types Of Mas Vaccines For Tilapiamentioning
confidence: 99%